The adaption of the Chinese version of the COVID Stress Scales as a screening instrument of stress: Psychometric properties during the COVID-19 pandemic - Xia, Lu; Lian, Qiaoping; Yang, Haibo; Wu, Daxing (Frontiers in Public Health, 2022)
The COVID Stress Scales (CSS) was used to access related distress concerning Corona Virus Disease 2019 (COVID-19). Based on China's epidemic prevention and control policies during the COVID-19 pandemic, the adaption of the Chinese version of the CSS was developed. Our study evaluated the reliability and validity of the Chinese adapted version of the CSS during the COVID-19 pandemic. An online survey was employed to construct a national sample of 2,116 participants in Mainland China. We examined the factor structure, internal consistency, convergent validity, discriminant validity, and concurrent validity. The results demonstrated that the six-factor solution for the Chinese adaptation of the CSS proved a good fit with the data after comparing the factor structure with the five-factor model. The six-factor model had good reliability and supported good convergent, discriminant, and concurrent validity of the CSS Chinese adaption. Overall, our findings supported the Chinese adapted version of the CSS as a psychometrically sound measure of stress during the COVID-19 pandemic in China.